A Systematic Review of Artificial Intelligence in Early Stroke Detection and Ongoing Neurological Monitoring: Nursing Implications - Deva P,; Dr. Hema.V.H,; Dr. Parameswari. M,; Dr. Motcharakkini. L,; Mrs. Jenifar Monisha.A, (The Bioscan, 2026)
Stroke is still a major cause of death and long-term disability around the world. To avoid permanent brain damage, it is important to diagnose it quickly and keep checking the person's neurological condition. Delays, differences between observers, and a lack of resources can make traditional clinical and radiological procedures difficult. The emergence of Artificial Intelligence (AI) has demonstrated potential as an effective tool for enhancing the early detection of strokes, automating monitoring procedures, and assisting in clinical decision- making. Still, the evidence is already out there about how well it works and what it means for nursing practice is not clear.